Territoriality in Post-conflict Neighbourhoods: Unravelling the Dynamics of Territorial Marks in Ile-Ife, Nigeria - Oluwasegun Odunlade; Albert A Abegunde (Alanya Üniversitesi, 2023)
ABSTRACT The pervasiveness of territorial marks in post-conflict neighbourhoods elicited this study. Relying on residents’ perceptions, the study explored the dynamics underpinning residents’ use of territorial marks. Primary data was collected by administering questionnaires to residents of various neighbourhoods within the study area. Physical observations were conducted to identify all residential neighbourhoods and categorised into three homogenous zones. From each homogenous zone, 30 neighbourhoods were purposively selected. In total, 2055 buildings were identified within these selected neighbourhoods. Thereafter, systematic sampling was employed, resulting in the selection of 206 residents living in separate dwelling units. Findings revealed significant territorial behaviour across all socioeconomic classes. Indigenous territorial marks were predominantly used across all income groups as elements used to communicate land ownership. The study concluded that while crime prevention may be correlated with territoriality, however, in post-conflict neighbourhoods, the need to demarcate land boundaries and communicate ownership was more important, as demonstrated in the adoption of indigenous elements as territorial marks. The paper concluded that in these neighbourhoods, territoriality is chiefly a land boundary regulation mechanism. The paper recommends clear-cut land policies in post-conflict communities while advocating for the recognition of indigenous territorial marks in Afro-centric literature.